OPTIMIZATION TOOLS IN MANAGEMENT AND FINANCE - Ferreira, Manuel Alberto M. (Acta Scientiae et Intellectus, 2024)
Through this paper, the most commonly used in management and finance optimization problems mathematical tools are presented, in a combined coherent way. The respective mathematical fundaments are synthetically outlined and the resolution methods are briefly described, hopping that this text functions as a manual in these matters.